Local Wisdom of the Togutil Tribe Community in Forest Conservation Efforts in Labi-Labi Village, North Wasilei District, East Halmahera Regency - Bayau, Edom (Agrikan Jurnal Agribisnis Perikanan, 2023)
The research aims to describe the forms of local wisdom related to the conservation of Togutil tribal forests in the village of Labi-Labi district of North Wasilei district East Halmahera. The problem tree in the research was more focused on the form of local wisdom that the Togutil tribe possessed in conserving forests. The method in this research is qualitative descriptive with the data sources used there are two: primary data sources and secondary data source. The data collection techniques used are: observations and interviews, library studies as well as documentary materials.research results revealed that the togutil tribe in the village of Labi-labi's life is still dependent on the forest and has local wisdom in conserving the forest. Local wisdom is the prohibition of protecting forests or called â€œbugoâ€ and local wisdom of using traditional medicines that come from the forest in treating diseases experienced by the community. The Togutil tribe has a spatial concept in managing the forest by dividing the use of the forest into three parts: jorame (Goyowa), gardens (Dumule) and forests (Hongana madutu). Conservation based on local wisdom also directly imply inining ecological balance so that forests remain awake and on the other hand also imply on the economy of communities. Itâ€™s necessary for the Government of East Halmahera district to protect Togutil tribal communities spread across the district and then to study and make local wisdom in forest conservation as a method that can be used in the preservation of forests in Eastern Halmahera district.